Resistance, resilience, and functional redundancy of freshwater bacterioplankton communities facing a gradient of agricultural stressors in a mesocosm experiment - Naíla Barbosa da Costa; Vincent Fugère; Marie‐Pier Hébert; Charles C.Y. Xu; Rowan D.H. Barrett; Beatrix E. Beisner; Graham Bell; Viviane Yargeau; Gregor F. Fussmann; Andrew Gonzalez; B. Jesse Shapiro (Molecular Ecology, 2021)
Agricultural pollution with fertilizers and pesticides is a common disturbance to freshwater biodiversity. Bacterioplankton communities are at the base of aquatic food webs, but their responses to these potentially interacting stressors are rarely explored. To test the extent of resistance and resilience in bacterioplankton communities faced with agricultural stressors, we exposed freshwater mesocosms to single and combined gradients of two commonly used pesticides: the herbicide glyphosate (0–15 mg/L) and the neonicotinoid insecticide imidacloprid (0–60 μg/L), in high or low nutrient backgrounds. Over the 43‐day experiment, we tracked variation in bacterial density with flow cytometry, carbon substrate use with Biolog EcoPlates, and taxonomic diversity and composition with environmental 16S rRNA gene amplicon sequencing. We show that only glyphosate (at the highest dose, 15 mg/L), but not imidacloprid, nutrients, or their interactions measurably changed community structure, favouring members of the Proteobacteria including the genus Agrobacterium . However, no change in carbon substrate use was detected throughout, suggesting functional redundancy despite taxonomic changes. We further show that communities are resilient at broad, but not fine taxonomic levels: 24 days after glyphosate application the precise amplicon sequence variants do not return, and tend to be replaced by phylogenetically close taxa. We conclude that high doses of glyphosate – but still within commonly acceptable regulatory guidelines – alter freshwater bacterioplankton by favouring a subset of higher taxonomic units (i.e., genus to phylum) that transiently thrive in the presence of glyphosate. Longer‐term impacts of glyphosate at finer taxonomic resolution merit further investigation.